Impact of the Early COVID-19 Pandemic on Gender Participation in Academic Publishing in Radiation Oncology - Nancy Anabaraonye; Chiaojung Jillian Tsai, MD, PhD; Hina Saeed, MD; Fumiko Chino, MD; Ekaete Ekpo; Sudeep Ahuja; Oscar Garcia, MPH; Robert C. Miller, MD, MBA, FASTRO (Advances in Radiation Oncology, 2022)
Purpose: There is a known gender gap in oncology publishing with worse disparities within specialty fields such as radiation oncology. There has been a significant increase in the number of articles submitted to academic journals during the pandemic. Several analyses have suggested that the pandemic has had a disproportionate effect on academic productivity of women in academia, as measured by article publication rates. Materials and Methods: The gender of first/co-first and corresponding/co-corresponding authors, as well as nonsenior versus senior status and manuscript type, for all articles published by Advances from its inception in December 2015 to the end of February 2020 was compared with those published between March 1, 2020, and May 31, 2020: the months during which the onset of the COVID-19 pandemic in North America began. Results: This examination of papers published during COVID-19 did not indicate a statistically significant decrease in the overall proportion of women publishing in Advances (P = .76). For nonsenior female authors, this proportion fell just short of statistical significance (39% vs 19%, P = .051). When only scientific manuscripts were considered, there was a statistically significant decrease in publications by nonsenior female first authors during the early months of the pandemic (37% vs 11%, P = .02). Conclusions: During the early months of the COVID-19 pandemic, nonsenior female researchers participated less in article publishing in radiation oncology.